A waveform clustering method for damage mode identification for composite laminates under hygrothermal environment. (November 2020) - Xu, D.; Liu, P.F.; Chen, Z.P.
Highlights : A waveform-based clustering model is introduced by employing several methods. The characteristic features of various damage modes are derived. The effect of hygrothermal aging on signal distortion is explored. The effects of hygrothermal aging on damage behaviors are investigated. Abstract: This work performs acoustic emission monitoring of damage behaviors in carbon fiber/ epoxy composite laminates during tensile loads under hygrothermal environment. First, a waveform-based clustering method is introduced by employing the wavelet packet decomposition (WPD), the Shannon's entropy, the cosine similarity and the clustering algorithm. Second, based on the clustering results, the characteristic features of various damage modes are derived. Finally, further investigation is carried out to explore the effects of hygrothermal aging on the damage source localization, damage initiation and evolution. From the theoretical analysis, several conclusions are obtained: 1. Fiber breakage behaves as a combination of matrix cracking, fiber/matrix interface debonding and delamination in the space of extracted features. 2. The frequency response of each damage mode is demonstrated to be degraded after hygrothermal aging. The principal features of fiber/matrix interface debonding and delamination are found to be significantly affected by hygrothermal aging as compared to other two damage modes. 3. The distortion of the principal feature of each micro-damage mode is found to be negligible with the damage accumulation, indicating the robustness of the method.